(untitled) (Teacher’s World: Journal of Education and Research, 2024)
Pre-service training and attitudinal background both are important to teach ‘sex education’ well in classroom. But lack of proper instruments to determine teachers’ attitudes toward sex education in Bangladesh paved way for the researcher to develop such scale. To develop the scale, initially 58 items were formulated using the deductive approach based on the five-point Likert’s scale method, of which 41 retained after a tryout and 36 items for the finalized scale. By using the convenience sampling method a pool of 130 samples was selected for the final data collection. After rigorous analyses, the scale’s average item-total correlation and Chronbach’s Alpha values were calculated as 0.465 and 0.773 respectively, which ensured its reliability. The items were developed as such they cover most topics of sex education in perspective of Bangladesh, thus establishing content validity. Finally, the Stanine scores or grades, ranging from 1 to 9, were calculated and assigned to the raw scores that were obtained by the samples, to interpret the findings in an understandable way. Based on the Stanine scores, the secondary teachers’ attitudes toward sex education were categorized in five categories as ‘very negative’, ‘negative’, ‘moderate’, ‘positive’ and ‘very positive’. Teacher’s World: Journal of Education and Research, 49 (2),53-74